(untitled) (Herald of the National Children’s Medical Center, 2022)
This article is devoted to the issues of integral assessment of the condition and predicting the outcomes of children with critical conditions at the prehospital stage of emergency medical care. Data from the case histories of 895 children were retrospectively studied and 143 children aged 12 to 18 years old were selected from them, who were in the ICU of the TashPMI clinic with somatic pathology and the presence of insufVciency in the function of vital organs, who were admitted through 96 the ambulance of the city of Tashkent. A comparative analysis of the statistical parameters of the MODS variable scale was carried out to determine the diagnostic ef ciency. It has been established that the MODS patient condition severity scale can be used in patients with critical conditions, both for individual prognosis of the outcome of the disease, and in assessing the effectiveness of intensive care at the stages of treatment. The use of scoring only the respiratory, cardiovascular and renal systems on the MODS scale can nd practical application in assessing individual outcome prognosis in critically ill patients.